Low geriatric nutritional risk index is a risk factor for death within 1 year following hip fracture. (17th May 2022) - Fujimoto, Yusuke; Setoguchi, Takao; Ishidou, Yasuhiro; Taniguchi, Noboru
Purpose: Hip fracture is common in older patients and is associated with high mortality and functional impairment. The Geriatric Nutritional Risk Index (GNRI) evaluates the risk of malnutrition-related complications, and the Barthel Index (BI) evaluates older patients' functional status. The study aim was to determine the risk factors for both death and decreased BI within 1 year after hip fracture. Methods: We retrospectively reviewed the records of 108 patients who were treated for hip fractures in 10 public or private hospitals from February to July 2007. Participating facilities comprised eight public or private hospitals with 200–499 beds, and two private or orthopedic hospitals with 20–199 beds. We evaluated several risk factors for death and lower BI within 1 year after hip fracture. Results: The mortality rate within 1 year postoperatively for patients who survived inpatient stay was 6.5% (7/108). The proportion of patients with decreased postoperative BI was 43.6% (44/101). Binomial logistic regression analysis showed that several factors, including low GNRI (odds ratio [OR]: 0.80; 95% confidence interval [CI: 0.68–0.93]), were risk factors for death within 1 year. Postoperative delirium (OR: 8.84 [1.52–51.6]), postinjury dementia (OR: 34.8 [3.01–402]), preinjury BI (OR: 1.05 [1.02–1.08]), and preinjury dementia (OR: 6.22 [1.73–22.4]) were risk factors for decreased postoperative BI. Conclusions: Our findings indicated that lower GNRI was a risk factor for death within 1 year of hip surgery and that delirium and dementia were among the risk factors for decreased BI 1 year after hip fracture.